INTERNALISTIC, EXTERNALISTIC AND COGNITIVE MOVEMENTS IN THE THEORY OF KNOWLEDGE BY NOAH LEMOS AND WAYS OF KONWLEDGE, OR TALK CURRICULUM BY TIM SPROD (Heritage, 2020)
When it comes to the theoretical and analytical approach and the study of the category of knowledge, one of the most frequently asked questions is the question of how far our knowledge reaches and what are its manifestations. Modern theory of konwledge, based on the postulates of ancient thinkers and philosophers of classicism, speaks of three types of konwledge :- propositional knowledge,- acquaintance knowledge and- „how to” knowledge.      The paper presents, explains and argues the basic characteristics of these tzpes of knowledge according to the clasivication of philosophers  and epistemologists Noah Lemos and Tim Sprod.     Also, the differences between the two general views on the nature of the justificaiton of knowledge, i.e. internalism an externalism, are presented and explained, followed by the naming of numerous factors that accompany them.
Keywords: knowledge, facts, justification, perspective, curriculum, internalisme, externalisme, perceptuality.